The Impact of Pipe Ø 0,5 Heater Length and Temperature on Ovality and The Difference in Pipe Thickness for Its Bending - Musholli Musholli; Sudarmaji Sudarmaji (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
Abstract, Ferrous metal is of material utilized mostly for many objects or kinds of stuff to help humans and their work easier. Low-carbon steel is one of the ferrous metal natures that could be utilized when transforms into more useful objects. There be cold as well as hot working to undertake. Molting by bending pipe includes cold working due to it being bent as its recrystallization temperature is lower. When the process is undertaken, the pipe dimension would be oval which needs to be examined by enumerating a lower-recrystallization temperature and whether or not to shrink the pipe ovality percentage. In addition, as the pipe is bent there would be changes in the pipe dimension because it would drives pulls as well as puts pressure on one of the cross-sectional areas so the pipe percentage of dimension/thickness changes should also be examined. Methods to apply are a series of experiments by firstly treating heating which is up to 650o C and bending pipe as its temperature goes lower between 410o C – 500o C. These two types of independent variables that differ only in their cross-sectional areas of heating also resulted in impacting on both ovality percentage and the pipe thickness of its cross-sectional area.